Compromise for the community: the early Kūfan soft Shīʿī traditionists and the formation of the four-caliphs thesis (al-Khulafāʾ Al-Rāshidūn) - Su, I-Wen (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper addresses the factors that may have lain behind ʿAlī’s elevation into being ranked among the four rightly guided caliphs by analysing the reception among proto-Sunnī traditionists of three early Kūfan traditionists noted for their Shīʿī sympathy — Wakīʿ b. al-Jarrāḥ (129–197 H/746– 812 CE), al-Faḍl b. Dukayn (130–219 H/748–834 CE), and ʿUbaydallāh b. Mūsā (d. 213–4 H/828– 9 CE). Analysis of the Kūfan traditionists’ scholarly standing suggests an overall acceptance of their membership in the traditionist community. This study argues that their commonalities — mild asceticism, belief in the uncreatedness of the Qurʾān, and a relatively positive attitude towards the first three caliphs — probably facilitated their convergence into the early Sunnī community. Viewed in the context of the struggles between the ahl al-ḥadīth and their opponents, it can be argued that the collective efforts of the traditionists to delineate their communal identity unavoidably involved concessions to the traditionists of different views, including acknowledgement of ʿAlī’s privileged status.